Growing Roses in Florida - Sydney Park Brown (EDIS)
Revised! Circular 334, a 4-page fact sheet by Sydney Park Brown, describes how to choose successful rose varieties for Florida, select a site and prepare the soil, plant and care for them. Includes references. Supersedes "Circular 334: Rose Culture" by S.E. McFadden and R.J. Black. Published by the UF Department of Environmental Horticulture, August 2007.